Climatic study of dust phenomenon in Semnan province and calculation of vertical dust flux by using GOCART model - Sara Karami; Nasim Hossein Hamzeh; Abbas Ranjbar (تحقیقات کاربردی علوم جغرافیایی)
Today, dust storms affect the lives of many people around the world and cause a lot of financial and human losses. Every year, Iran is affected by dust storms caused by internal sources and external dust sources located in neighboring countries. Semnan province has several dust-producing sources due to its geographical location, that affect not only this province, but also the neighboring provinces. The purpose of this study is to investigate the dust phenomenon of Semnan province and its monthly changes in the 15-year period, between 2003 and 2017. For this purpose, meteorological stations data of the province and the aerosol optical depth of satellite product have been investigated. Also, GOCART model has been used to estimate the amount of dust emissions from this region and to determine the vertical dust flux in Semnan province. The study of average dust flux showed that the highest values ​​of dust flux was in the southeast of Shahroud and then in the south of Shahroud, Damghan and Sorkheh. A monthly investigation showed that in all months, the average AOD in the southern half of Semnan province was higher than in the northern half. The highest levels of AOD were in May, April and June, and the highest amounts of dust flux were observed in March, June and July. Also, the prevailing wind direction was northeast and northeast, and this factor causes dust particles rising from this region and dust loading in the south of Semnan province and areas of Isfahan, Yazd and South Khorasan provinces.